Employee engagement: development of a new measure. (2019) - Ababneh, Omar M.A.; LeFevre, Mark; Bentley, Tim
It is claimed that organisations investing in employee engagement will reap significant benefits in terms of employee productivity, achievement of organisational goals, customer satisfaction, and talent retention. However, fundamental issues revolving around the meaning, measurement, and key antecedents of employee engagement still require further research attention. In response to these issues, this study aimed to develop a reliable and valid engagement scale. Guided by Ababneh and Macky's (2015) operational definition, a new measurement tool, including items that tap each component of the engagement construct, was developed. This study provides empirical evidence supporting the dimensionality of the engagement construct and proposes additional dimensions (goal-identification, task performance, positive emotions, persistence, and discretionary effort) to be considered when measuring the construct. Further, this study provides empirical evidence about the discriminant validity of employee engagement when it is compared to other well-established attitudinal constructs (job satisfaction, job involvement, organisational commitment). Also, this research provides practical recommendations on how to execute certain HR practices (measuring employee engagement, training and development, performance management) in a manner that fosters an engaging climate at the workplace and enhances employees' levels of engagement.